Chronologized Picture Odyssey of Tent Pegging in Sports:Cultural and Historical Perspective of Pakistan (Journal of Asian Development Studies, 2023)
Tent Pegging sport in Pakistan is not only a display of prowess, but to the nation, it is a livingtestament due to its connectivity with its historical past. This article aims to apprise, edify andengross readers about tent pegging and concisely introduce its origin, history, culturalimplications, and significance. It personifies the sportsmanship, spirit of unity, linguistic,geographical and cultural divides. Pakistani culture is bonded through the Tent Pegging in ashared skill, spirit of competition and same appreciation for its tradition in the region. TentPegging is a platform for nurturing the talents of Pakistani youth and is now a source of inspirationfor all. The rider's dedication is to preserve the tradition and advance Tent Pegging throughoutthe region through organizing events and competitions. As a result, their hard work assists as aninspiration, encouragement and beacon for future generations of the area. Looking ahead, it isdomineering that we constantly support and celebrate this sport in Pakistan. This entails devotingto facilities, endorsing awareness and providing opportunities for young players and riders tosharpen and hone their skills.